Religion and identity in post-conflict societies - Ammicht Quinn, Regina; Wacker, Marie-Theres; Babić, Mile; Grozdanov, Zoran (Concilium, 2015)
Part One: The Puzzle of Identity -- Part Two: Identities in the Vortex of Conflict -- Part Three: The Religious Potential for peace -- Part Four: United Europe: An Unfinished Project -- Part Five: Theological Forum